A study of soil bacterial communities of fildes peninsula, King George Island (South Shetland Islands), Antarctica - Foong, Choon Pin (2011)
There is sparse information on the bacterial diversity of Filldes Peninsula, King George Island of the maritime Antarctic. A metagenomic approach was used in this study to determine the dominant bacterial population in the soil from the lakes, river and glacier at the Fildes Peninsula, King George Island. Total of ten soil and sediment samples were studied for bacterial diversity using the PCR-DGGE approach targeting for the 165 rRNA gene. About 0.12 to 4.80 μg of DNA was extracted from one gram of soil using the hot enzymatic direct lysis DNA extraction method. Partial 16S rRNA gene product was amplified using the GC357f and 907r primer set, and the amplicon was further resolved using DGGE. Ten to 100- fold dilution of the template or an addition of 10 μg/μI of bovine serum albumin (BSA) in the PCR reaction had successfully reduced the inhibitory effect of the contaminants on the laq polymerase. All the soil samples have different profiles of predominant bands. The predominant bands were excised for sequence determination and bacterial identification. A total of 99 bands and 299 clones were selected from ten locations: Antarctic Lake (AL), GFZ Lake (ZL), Estrellas Lake (EL), Playa Elefantes (PE), Minas River (MR), Collins Glacier (CG), Kitiesh Lake (KL), Selem Lake (BL), Geografos Lake (GL) and oil tank area (OT). After grouping these sequences in different operational taxonomic units (OTUs) (similarity <97%), they were categorized into RDP-designated phylum: Bacteroidetes (27.4%), Proteobacteria (25.7%), Acidobacteria (13.1%), Gemmatimonadetes (4.0%), Firmicutes (4.0%), Actinobacteria (3.4%), Chloroflexi (1.7%), Nitrospira (1.1%), Cyanobacteria (1.1%), WS3 (1.1%), Deionococcus-Thermus (0.6%), Spirochaetes (0.6%) and BRC1 (0.6%). Another 15.4% of the sequences were grouped into unclassified bacteria. Almost 90% of the OTUs have closest relative with uncultured bacterium from the NCBI GenBank database. About 79% of the OTUs had been retrieved in regions which were outside from the Antarctic continent. Acidic soils demonstrated lower diversity of bacteria where two weakly acidic soils PE and OT had the lowest Shannon diversity index. There was no obvious correlation for the changes of bacterial communities between those areas influenced by human activities and less-disturbed by human activities except in the oil tank area. Several phylotypes affiliated with hydrocarbon-degrading bacteria were detected in oil tank area.